1987
DOI: 10.1128/mcb.7.5.1973
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous expression of c-myc in BC3H1 cells partially inhibits but does not prevent myogenic differentiation.

Abstract: Myogenic differentiation is obligatorily coupled to withdrawal of myoblasts from the cell cycle and is inhibited by specific polypeptide growth factors. To investigate the potential involvement of c-myc in the control of myogenesis, the BC3H1 muscle cell line was stably transfected with a simian virus 40 promoter:c-myc chimeric gene. In quiescent cells in 0.5% serum, the exogenous c-myc gene was expressed at a level more than threefold greater than the level of endogenous c-myc in undifferentiated, proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 41 publications
2
54
1
Order By: Relevance
“…In addition to promoting tumor formation, anchorage-independent growth, and cellular immortalization, expression of transforming oncogenes inhibits cellular differentiation in several different cell lineages. In muscle cells, expression of oncogenic tyrosine kinases (v-src and v-fps), growth factor receptors (v-erbB), nuclear oncogene products (v-myc, c-myc, v-erbA, and E1A), and the activated forms of signal-transducing G proteins (H-ras and N-ras) can inhibit terminal differentiation to various extents (5,7,10,14,30,31,37,45). We previously demonstrated that ras and fos prevent myogenesis by inhibiting expression of MyoD (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting tumor formation, anchorage-independent growth, and cellular immortalization, expression of transforming oncogenes inhibits cellular differentiation in several different cell lineages. In muscle cells, expression of oncogenic tyrosine kinases (v-src and v-fps), growth factor receptors (v-erbB), nuclear oncogene products (v-myc, c-myc, v-erbA, and E1A), and the activated forms of signal-transducing G proteins (H-ras and N-ras) can inhibit terminal differentiation to various extents (5,7,10,14,30,31,37,45). We previously demonstrated that ras and fos prevent myogenesis by inhibiting expression of MyoD (19).…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect has been observed in myoblasts constitutively expressing v-jun mRNA, as myotubes that form in these cells have lost Jun nuclear staining (Grossi et al 1991;Su et al 1991). Also, as constitutive expression of c-myc mRNA has been shown to block myogenesis to varying extents under different experimental conditions (Schneider et al 1987;Miner and Wold 1991), it will be of interest to see whether levels of Myc protein in the nuclei of these cells determine the differentiated state of the cell.…”
Section: Genes and Developmentmentioning
confidence: 99%
“…Recent evidence indicates that cyclins are downstream targets of c-Myc in cell cycle activation (Jansen-DuÈ rr et al, 1993;Hoang et al, 1994;Philipp et al, 1994;Rudolph et al, 1996). Ectopic expression of c-myc inhibits terminal dierentiation in a variety of cell lines including mouse erythroleukemia (MEL) cells (Coppola and Cole, 1986;Prochownik and Kukowska, 1986), F9 teratocarcinoma cells (Griep and Westphal 1988), monoblastic U-937 cells (Larsson et al, 1988), and myoblasts (Schneider et al, 1987;Miner and Wold, 1991). Overexpression of c-myc has been shown to inhibit dierentiation of 3T3-L1 cells possibly by precluding the entry of cells into a distinct predifferentiation stage in G0/G1 (Freytag, 1988).…”
Section: Introductionmentioning
confidence: 99%